Seizing Center Stage: Ecosystem Services, Live, at the Convention on Biological Diversity!. Issue 1 (March 2013) - Suarez, Daniel; Corson, Catherine
Over the past decade, the concept of ecosystem services has become a central guiding framework for environmental conservation. Techniques of valuation, payments to protect ecosystem services, and efforts to put a price on nature increasingly characterize environmental policy. We analyze the 10th Conference of the Parties (COP-10) to the Convention on Biological Diversity (CBD) as a critical moment in the production of ecosystem services as a discourse. Through analysis of specific examples of the rollout, performance, and strategic deployment of ecosystem services, particularly as embodied in The Economics of Ecosystems and Biodiversity project (TEEB) at CBD/COP-10, we illustrate how arguments justifying ecosystem services became persuasive and compelling in the social space of the meeting. We examine the prevalence of a narrative that relies on three successive claims: (1) conservation has failed to conserve biodiversity, which has catalyzed a pending ecological crisis; (2) this crisis is caused by incorrectly priced nature and insufficient financing for conservation; and (3) the economics of ecosystem services provides the means to attract new financial flows, to neutralize political opposition, and to save biodiversity. The CBD/COP-10, we argue, provided a stage for the performance of this narrative, the alignment of actors from the private, public and non-profit sectors around ecosystem services, and the institutionalization of its tenets in policy documents and project financing— all of which worked to constitute the hegemony of ecosystem services. We conclude by asserting that, as conservationists embrace ecosystem services, at the expense of alternative models, they reproduce it as a discourse, thus constituting and reinforcing its hegemony, and the conditions that originally limited their choices.